Canadian constitutional law - Mathen, Carissima; Macklem, Patrick; Albert, Richard (Emond, 2022)
"In this new edition, Patrick Macklem will be joined by a new co-general editor, Carissima Mathen, a leading constitutional expert and professor at the University of Ottawa. In addition to providing a comprehensive introduction to Canadian constitutional law, leading cases, and insightful commentary and discussion, Canadian Constitutional Law, 6e also looks to provide new insight into the book with the addition of new authors, a fresh perspective on many constitutional matters, and expand materials on Indigenous issues in various chapters throughout the book, being informed by the TRC Calls to Action. By doing so, the book will further distinguish itself as the leading book on Canadian constitutional law for use by law schools across the country."– Résumé de l'éditeur.